Conceptualising the influence of total quality management and organizational performance in Klang Valley service industry - Omar, Siti Sarah; Ariffin, Zailin Zainal; Abdullah, Aida Nasirah; Mahadi, Nomahaza; Mokhtar, Fahirah Syaliza; Azman, Nur Azmiza (American Scientific Publishers, 2018)
Studies on Total Quality Management (TQM) practices in service industry are scarce. This conceptual study sought to investigate the TQM best practices dimensions that could be applied by the service industry. The research in TQM in Malaysia have been explored quite extensively focusing particularly on manufacturing industry but not in other industry including service industry. The preliminary result indicated that seven dimensions of TQM could be applied for TQM best practice. The discussion and arguments in this conceptual study would be used further in the actual study to address the lacuna in research on TQM and provide insights for organizations to use TQM best practices in the service industry today. The main aim of this study is to determine the best practice dimensions of TQM in Malaysia’s service industry, taking into consideration the dimensions proposed by previous research (i.e.: leadership, supplier management, strategic planning, human resource management, customer focus, information and analysis and process management). This study will further identify how TQM could influence service industry organizational performance in Malaysia to fill the gap in TQM and service industry.